VISUAL COMMUNICATION IN PUBLIC ART: A SYSTEMATIC REVIEW OF APPROACHES TO PLACE-MAKING (2015–2025) - Arjuna, Diean; Hapiz, Hana Yazmeen; Ibrahim, Yuhanis (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Public art has evolved from static monuments and decorative sculptures into interactive, dialogic and community-driven interventions that increasingly determine how public spaces are perceived, experienced and remembered. At the core of these transformations lies visual communication, encompassing the strategic use of imagery, colour, typography, spatial graphics and emerging digital media to convey meaning, foster collective memory and strengthen a sense of place. Although the relationship between visual communication and placemaking is widely recognised, scholarship over the past decade remains fragmented across architecture, cultural geography, design studies and communication theory, creating the need for a consolidated synthesis of approaches. This study presents a systematic literature review of peer-reviewed studies published between 2015 and 2025 that examine visual communication within public art contexts and its relationship to placemaking outcomes. Guided by the PRISMA 2020 protocol, comprehensive searches of Scopus and Web of Science yielded 486 records; after duplicate removal, screening of titles and abstracts, full-text eligibility assessment and quality appraisal using a modified CASP checklist, 138 articles were retained for thematic analysis. The review identifies three dominant strands: first, semiotic and symbolic representation, encompassing murals, memorials, sculptures and environmental graphics that embed heritage codes and civic narratives; second, participatory visual narratives, involving co-created and tactical urbanism artworks that enhance community pride, inclusivity and the legibility of space; and third, digital hybrid interventions, including augmented reality murals, projection mapping and immersive media that mediate the relationship between site, artwork and audience perception. Synthesising these strands, the review proposes a conceptual framework that traces visual communication modes to audience interpretation to emotional and behavioural response to place attachment, highlighting a decisive shift from object-centred aesthetics toward communication-centred and audience-responsive public art practices while underscoring persistent research gaps in under-represented regions of the Global South.